ANALYZING STUDENTS’ DIFFICULTIES IN MAINTAINING THEIR COHERENCE AND COHESION IN WRITING PROCESS - Ratu Nur Faradhibah; Nur Aliyah Nur (Universitas Islam Negeri Alauddin Makassar, 2017)
This research concerned on writing skill, especially about coherence and cohesion as the important elements in writing. The aim of this research was to find out the students’ difficulties in maintaining their coherence and cohesion in writing process. This research employed descriptive qualitative study. It was conducted in English Education Department of Tarbiyah and Teaching Science Faculty of UIN Alauddin Makassar. The subject of this research was the students of the Department of Tarbiyah of English group 1 and 2 in academic year 2016/2017. The total numbers of students were 36 students. Written test and interview was the instrument used to collect the data in this research. The findings of this research showed that there were some difficulties faced by the students in maintaining their coherence and cohesion in writing process, specifically in determining and stating their ideas, fulfilling the supporting details, and using the proper signals and spelling as well as punctuation.